STRATEGIC POLICY AND ENVIRONMENTAL MANAGEMENT FOR DRIVING GREEN ROAD CONSTRUCTION IN THAILAND - PAKDEEARPORN, DISAYAPAT; SANGNAK, Danupon (Thai Interdisciplinary and Sustainability Review, 2026)
This documentary research examines the opportunities and challenges of implementing green road construction in Thailand to achieve sustainable development. Addressing the severe environmental impacts of conventional road building, specifically PM2.5 and PM10 air pollution, the study employs Porter’s Five Forces and PESTLE analysis to evaluate strategic industry dynamics and macroeconomic policy contexts. The findings reveal that while national bio-circular-green economic policies, increasing public environmental awareness, and technological advancements provide substantial opportunities for green infrastructure, critical barriers remain. These challenges include stringent budget limitations, insufficient technological readiness, human resource constraints, and inconsistent regulatory enforcement. To overcome these systemic obstacles, this study proposes an integrated, proactive policy framework. This comprehensive approach emphasizes synergistic stakeholder collaboration, continuous monitoring of environmental impacts, and the systematic integration of innovative construction technologies. Ultimately, this strategic roadmap provides actionable insights for policymakers and industry practitioners to mitigate structural constraints, foster sustainable economic growth, and elevate Thailand’s green public infrastructure to meet international environmental standards.